Mathematical Reasoning Ability as a Tool to improve Mathematical Literacy - Siti Norhidayah (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
Mathematical reasoning is one of the competencies needed to improve mathematical literacy. Mathematical reasoning is very influential in relation to other sciences and in daily life. This research is a descriptive research with the purpose of describing mathematical reasoning ability of Semester 1 students of Mechanical Engineering Study Program of Balikpapan University. The result of the research shows that there is a good mathematical reasoning in Mechanical Engineering 1st Semester Class A1 Academic Year 2023/2024. With good mathematical reasoning, it can be said that their mathematical literacy is also good enough. Mechanical Engineering students who have good mathematical reasoning will be very supportive in understanding other sciences, especially science in the field of Mechanical Engineering. The problems that arise in the process of mathematical reasoning of Mechanical Engineering Semester 1 students include not understanding the meaning of the problem command, difficulty starting the work steps, lack of accuracy when operating numbers, inability to use certain theories / formulas / rules in solving problems, inability to conclude answers, usually the answer only stops at the calculation result without concluding the results. For students whose achievement of mathematical reasoning ability indicators is still low, it can be helped by often practicing working on problems that require mathematical reasoning. This is one way for teachers to improve their students' mathematical reasoning skills.